Effectiveness study on printed campaign for eco-tourism. A case study : Nur Lembah Pangsun, Eco-Resort / Adzrool Idzwan Hj Ismail - Ismail, Adzrool Idzwan (2006)
Introduction: This research is concerned with a specific genre on "Effectiveness study on printed campaign for eco-tourism, a case study: Nur Lembah Pangsun, Eco-Resort that was documented within the durations 4 months (December 2005 till the 30 March 2006). Statements of problems: It is estimated that about 7 to 10 per cent of all overseas tourist are involved in eco-tourism activities, while up to 14 per cent express an interest in walking, hiking and trekking. This amounts to about 512,000 to 1,024,000 overseas tourists per year. This study hopes to find out what the best way is to attract tourist to visit and participate in eco-tourism activities at rain forest/reserve forest around Kuala Lumpur and Selangor. Methodology: Applied research methods use quantitative measurement and analysis, experimental designs survey to provide information to help serve the community (Banks 1997, 111, Cameron et al. 1992). Finding: Result suggested that; an appealing image brousher about nature given as a gift at point of entry to the country will attract tourist to Malaysia eco-tourism sport. The finding of this research will be usefull for eco-tourism agencies. Conlusion: The conclusion for this research is that image plays an important role in influencing the public. Recommendations: The research of graphic elements also should be taken into account and evaluated in the future. The effectiveness of image layout and composition also can enhance and further influence the reader's mind.